$\begin{array}{1 1}(A)\;m = -2 ; c = \large\frac{5}{3} \\(B)\; m = 2; c = -\large\frac{5}{3} \\(C)\; m = \large\frac{1}{2} ; c = \large\frac{5}{3} \\(D)\;m = -\large\frac{1}{2} ; c = -\large\frac{5}{3} \end{array} $

- Slope intercept form of an equation is $y=mx+c$ where $m$ is the slope and $c$ is the $y$ intercept

Given equation is $6x+3y-5=0$

This can be written as

$ \qquad 3y=-6x+5$

$ \quad \Rightarrow y = -\large\frac{6}{3}$$x+\large\frac{5}{3}$

or $ y= -2x+5$

This is of the form $y=mx+c$

Here $m = -2$ and $ c = \large\frac{5}{3}$

Hence the slope is $-2$ and $y$ intercept is $ \large\frac{5}{3}$

Ask Question

Tag:MathPhyChemBioOther

Take Test

...